2021
DOI: 10.1016/j.jpeds.2021.06.062
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Evidence for Assessing Treatment Effectiveness and Safety in Pediatric Populations

Abstract: This article is endorsed by the International Society for Pharmacoepidemiology (ISPE). D.H. is supported by the National Institute of Arthritis and Musculoskeletal and Skin Diseases of the National Institutes of Health (K23AR070286 and R01AR074436) and received grant funding from Danisco USA Inc. M.Bu. is a fulltime employee of Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA and holds stock in Merck & Co., Inc., Kenilworth, NJ, USA.M.Bl. declares no conflicts of interest. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The authors observed an increase in depression and anxiety in children who initiated PPI treatment, a finding consistent across multiple secondary and sensitivity analyses. Pharmacoepidemiological studies, such as the one by Wang et al 4 can provide valuable insights on pediatric drug safety, particularly when randomized controlled trials (RCTs) are unavailable, underpowered, or infeasible to address outcomes of interest. Understanding the strengths and weaknesses of real‐world data from large healthcare databases for pharmacoepidemiological research and associated threats to validity are key to interpreting findings.…”
Section: Commentarymentioning
confidence: 99%
“…The authors observed an increase in depression and anxiety in children who initiated PPI treatment, a finding consistent across multiple secondary and sensitivity analyses. Pharmacoepidemiological studies, such as the one by Wang et al 4 can provide valuable insights on pediatric drug safety, particularly when randomized controlled trials (RCTs) are unavailable, underpowered, or infeasible to address outcomes of interest. Understanding the strengths and weaknesses of real‐world data from large healthcare databases for pharmacoepidemiological research and associated threats to validity are key to interpreting findings.…”
Section: Commentarymentioning
confidence: 99%
“…1,9,10 However, the use of RWE is currently not as widely used in pediatrics, and there is a need to further leverage administrative and EHR databases to study effectiveness and safety of medications in pediatric populations. 2,11 As RWD becomes increasingly important in epidemiology and pharmacoepidemiologic research, 11,12 an overview of RWD sources available to researchers is needed. In 2015, McMahon et al cataloged 20 unique databases in North America that captured postmarketing safety data in children including adverse events to pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Real‐world evidence (RWE) generated during routine clinical practice is increasingly critical in decision‐making processes related to medicinal products, including regulatory approval, patient access, health technology assessment, safety evaluation, and post‐approval lifecycle management 1,9,10 . However, the use of RWE is currently not as widely used in pediatrics, and there is a need to further leverage administrative and EHR databases to study effectiveness and safety of medications in pediatric populations 2,11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to a recent grant award from FDA, the International Neonatal Consortium (INC) has an opportunity to collate and evaluate real world data (RWD) sources to assess their value in informing various aspects of neonatal drug development. There is a greater recognition that such data may provide an important key to assess the heterogeneity of neonatal populations as well as the significant variability in respect to the current standard of care ( Horton et al, 2021 ). While this report provides a broad landscape of the available data sources to inform a family of models to assess BPD disease progression, it is the RWD that represents the new Frontier in this effort.…”
Section: Introductionmentioning
confidence: 99%